Equity Analysis of Local Government: A Case Study of Deli Serdang Regency, North Sumatra Province, Based on Government Financial Reports and IFRS Principles - Putri Tunggal Dewi; Kayyisa Fahani; Iskandar Muda (International Journal of Economics, Commerce, and Management, 2025)
This study provides a detailed equity analysis of the Deli Serdang Regency local government by evaluating its financial statements from 2020 to 2023 and interpreting results through the lens of International Financial Reporting Standards (IFRS) and public sector accounting principles. The analysis examines trends in assets, liabilities, and equity, computes key financial ratios, and discusses implications for fiscal sustainability, transparency, and governance. The study combines quantitative ratio and trend analyses with a qualitative review of notes to the financial statements and a reconciliation exercise mapping local government reporting (SAP/APBD disclosures) to IFRS/IPSAS concepts. Findings (illustrative data) show a positive but modest growth in equity, persistent dependence on intergovernmental transfers, and opportunities to improve asset valuation and liability recognition practices. The paper concludes with practical recommendations for policy-makers and local finance managers and suggests a road map for incremental IFRS-aligned reporting in the local government context.